SYSTEM DESIGN OF INFORMATION MANAGEMENT FUND ADMINISTRATION AND PUBLIC ADMINISTRATION (CASE STUDY : RW 01 KELURAHAN CIPONDOH INDAH) - Ikhsan, Muhammad; Saragih, Hoga (Journal of BUSINESS INFORMATION SYSTEM, 2016)
All the recording of the events of administration of population, births, deaths, residents moved in and fund the citizens must first noted by RT, then reported to the RW, and continue to the village. In the case study Cipondoh Indah Village recording system previously encountered many obstacles due to the storage of data in hardcopy resulting data on demographic events are broken or missing. The process of delivering a report on population is not real time because the wait for the report of each device associated. But to run the administration and citizens administration fund requires an information system that is able to accommodate all of the recording of the events that occur in the population. The purpose of this research is to produce a design of information systems administration and fund management resident population online in the form of web-based dashboard using design methods WISDM (Web Information System Development Methodology) results will be applied to hamlet 01 Cipondoh Indah Kota Tangerang. Kata kunci: Information Systems, Web Dashboard, Web Information Systems Development Methodology (WISDM)